Using an observer rating method to assess the effects of rotational stocking method on beef cattle temperament over time - Rocha Gois, Karen Camille [UNESP]; Ceballos, Maria Camila [UNESP]; Sant'Anna, Aline Cristina [UNESP]; Rodrigues Paranhos da Costa, Mateus Jose [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2016)
The objectives of this study were to propose behavioral-based definitions for the adjectives used in an observer rating method, and to use this approach to characterize temperament over time in cattle kept under rotational stocking method. We also analyzed the feasibility of the rating method under commercial cattle farming conditions. We evaluated the temperament evolution of 1,979 pure and crossbred Nellore young bulls over time on three commercial farms located in Northeastern Para State, Brazil. All animals were kept under a rotational stocking method. The observer rating method included 14 behaviorally predefined adjectives for which we defined the minimum and maximum scores. The first factor was considered a qualitative temperament index (QTI) ranging from 'relaxed'/'calm'/'comfortable' to 'fearful'/'agitated'. According to the QTI, cattle temperament improved over time. For Farms A and B, QTI decreased over evaluations, and for Farm C, QTI did not differ from the first to the second evaluations, but decreased from the second assessment onwards. The observer rating method consisting of behaviorally pre-defined adjectives is an adequate indicator of cattle temperament that may be feasible under farm conditions. The method captures different aspects of cattle temperament and distinguishes between slight variations in cattle body language that successfully reveal temperament changes over time.
Keywords: behavior; qualitative behavior assessment; rotational stocking method